Trapped in a Daydream: Daily Elevations in Maladaptive Daydreaming Are Associated With Daily Psychopathological Symptoms - Soffer-Dudek, Nirit; Somer, Eli (Frontiers in Psychiatry, 2018)
Background: Maladaptive Daydreaming (MD) characterizes individuals who engage in vivid, fanciful daydreaming for hours on end, neglecting real-life relationships and responsibilities, resulting in clinical distress and functional impairment. Sufferers have embraced the term MD in cyber-communities devoted to this problem because it seemed to uniquely fit their experience and since existing diagnostic labels and their therapies seemed inadequate. However, scientific research in the field has been scarce, relying on cross-sectional or case study designs. Existing knowledge on MD suggests the involvement of dissociative and obsessive-compulsive symptoms, as well as positive reinforcement comparable to processes in addiction disorders. The present study aimed to rigorously explore factors that accompany MD employing a longitudinal daily-diary design, hypothesizing that temporal increases in MD will associate concurrently with, and will temporally precede, other symptoms and emotional changes. In addition, we aimed to explore which symptoms may act as precursors to increases in MD, in order to identify possible mechanisms bringing about daydreaming in these individuals. Methods: In a sample of 77 self-diagnosed individuals with MD we assessed relevant daily symptoms for 14 days, including MD, depression, general anxiety, social anxiety, obsessive-compulsive symptoms, and dissociation, as well as positive and negative emotion. Results: Increases in MD were strongly related to concurrent increases in all other symptoms and negative emotion, and to decreased positive emotion. Obsessive-compulsive symptoms, dissociation, and negative emotion also temporally followed MD. Obsessive-compulsive symptoms were the only consistent temporal antecedent of MD. Conclusions: MD and obsessive-compulsive symptoms coincided in what seems to be a vicious cycle; understanding possible shared mechanisms between these symptoms may inform our understanding of the etiology of MD. For example, Serotonin levels may possibly be involved in the development or maintenance of this condition. The findings may also provide clues as to potentially beneficial interventions for treating MD. For example, perhaps utilizing response prevention techniques may be useful for curbing or intercepting unwanted daydreaming. Future studies on MD should address its compulsory nature.